Conceptual framework for measuring the acceptance of Smartwatch to check blood pressure and pulse transmission time - Kandhro, Rukhsana; Korejo, Imtiaz Ali; Koondhar, Muhammad Yaqoob; Korejo, Masroor Ahmed Korejo; Maher, Zulfiqar Ahmed; Depar, Mansoor Hyder; Shah, Asadullah (MUK Publications & Distributions, 2021)
Innovative research and development in Information Communication and Technology have reshaped our daily life. Use of ICT tools in medicine has great impact on our daily life. Nowadays our life is at is at major risk of health diseases. Hypertension is becoming a chronic disease in our society. To avoid hypertension, use of Smartwatch is better option. Because most of the peoples are not aware of diseases which occurs due to the blood pressure. If these diseases are not diagnosed at early stage, then it is too difficult to control. So, by using Smartwatch they can get update of their health and will get proper treatment. But technology itself cannot guarantee the usage of technology so this research is to identify the motivating external factors that affect the students to use Smartwatch for check blood pressure and pulse transit time. Hyderabad and Jamshoro users of smartwatch was the target population of this research. Stratified random sampling techniques was used in this research. Technology acceptance model (TAM) was used with three external factors Self efficacy, Subjective norms and Trust. Quantitative research methodology has been used for this research. After data collection SPSS and SmartPLS was used for data analysis and hypothesis testing.